Penanaman Nilai-Nilai Kearifan Lokal Dayak Ma’anyan Dalam Pembentukan Karakter Anak Usia Dini Di Kabupaten Barito Timur - Tutik Haryani (Jurnal Ilmiah Kanderang Tingang, 2022)
Character education has become a central theme since the last few years in the development of education in the country. Character education must be implemented from an early age because at an early age children are in the golden age, and at that age the ability to absorb information in religious, moral, cognitive, and social emotional aspects occurs quickly. Therefore, educators and parents have great opportunities to shape children's characteristic for the better. One of the goals of education is to shape one's personality. The personality in question is the character value of an individual, because character values ​​must be instilled from an early age. One of the lessons that is fun and stimulates the character values ​​of early childhood is learning based on local wisdom, namely Dayak Ma'anyan. Many values ​​of Dayak Ma'anyan local wisdom that builds the character of early childhood, including in the local wisdom values ​​of Dayak Ma'anyan, are namely: “Dundung rueh rare, petan sangkuh benet”, “Mira tanjung pikayeman ukur baya rantau pirupakan bayu”, ”Haut wehu, ilahuah iselem”, “Kukui witang ada witus, surung jawu ada pegat”, “Umpe lutek alap tanang”, dan “Nyalah karewau napait hang urung”.